Muslim Contestations over Islam and the State Relationship: A Critical Appraisal - Showkat Ahmad Wagay (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Recent years have seen a proliferation of academic writing on the relationship of Islam and state from both the Muslims and non-Muslim academicians alike. Mostly, this academic writing used the trend of Islamism as a peg to ponder about the relationship of Islam and the state. The advocates of this trend hold the belief that the state is the nerve centre of Islam. They believed that Islam is a holistic religion and denies the separability of religion from politics and considers political power as an indispensable mechanism to achieve the ends of Islam. They posit Islamic governance as an authentic and correct form of polity. The other trend claims that Islam is primarily silent on the issue of the “state,” and that notions of an “Islamic state” or caliphate are dictatorial and antithetical to traditional Islam, though Islamic values can inform the individual in their role as a citizen within a democratic state. They proposed an alternative conceptualization of state-religion relations that avoids identifications of the state with any particular religion and ideology. Thispaper will briefly examine the genealogy of these two competing claims, and it will also highlight the arguments and counter-arguments of the representative scholars of bothclaims.